Molecular definitions of autophagy and related processes. (8th June 2017) - Galluzzi, Lorenzo; Baehrecke, Eric H; Ballabio, Andrea; Boya, Patricia; Bravo‐San Pedro, José Manuel; Cecconi, Francesco; Choi, Augustine M; Chu, Charleen T; Codogno, Patrice; Colombo, Maria Isabel; Cuervo, Ana Maria; Debnath, Jayanta; et al.
Abstract: Over the past two decades, the molecular machinery that underlies autophagic responses has been characterized with ever increasing precision in multiple model organisms. Moreover, it has become clear that autophagy and autophagy‐related processes have profound implications for human pathophysiology. However, considerable confusion persists about the use of appropriate terms to indicate specific types of autophagy and some components of the autophagy machinery, which may have detrimental effects on the expansion of the field. Driven by the overt recognition of such a potential obstacle, a panel of leading experts in the field attempts here to define several autophagy‐related terms based on specific biochemical features. The ultimate objective of this collaborative exchange is to formulate recommendations that facilitate the dissemination of knowledge within and outside the field of autophagy research. Abstract : Autophagy‐related responses are described in an increasing number of distinct biological contexts. This review discusses the use of appropriate terms for autophagic processes with the aim to provide recommendations and avoid confusion in the field of autophagy research.